If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7S(r + -3) = 0 Reorder the terms: 7S(-3 + r) = 0 (-3 * 7S + r * 7S) = 0 (-21S + 7rS) = 0 Solving -21S + 7rS = 0 Solving for variable 'S'. Move all terms containing S to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), '7S'. 7S(-3 + r) = 0 Ignore the factor 7.Subproblem 1
Set the factor 'S' equal to zero and attempt to solve: Simplifying S = 0 Solving S = 0 Move all terms containing S to the left, all other terms to the right. Simplifying S = 0Subproblem 2
Set the factor '(-3 + r)' equal to zero and attempt to solve: Simplifying -3 + r = 0 Solving -3 + r = 0 Move all terms containing S to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + r = 0 + 3 Combine like terms: -3 + 3 = 0 0 + r = 0 + 3 r = 0 + 3 Combine like terms: 0 + 3 = 3 r = 3 Add '-1r' to each side of the equation. r + -1r = 3 + -1r Combine like terms: r + -1r = 0 0 = 3 + -1r Simplifying 0 = 3 + -1r The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
S = {0}
| 1+3x=5(15-x) | | .4x+2.4=4.25 | | 9x^16=0 | | 4x^2-8x-62=0 | | 3x+x+1=9x-5x+2 | | .4x+2.4=4.24 | | 3(8c-4)=21+5c | | 2p+5=-12 | | -2x=-10y+3zx+1 | | 6x+18x-9=6(4x+1) | | 3-11x=13-x | | 16=5x-6 | | (34x+56y)+(41x-14y)= | | Z-4-4z=1 | | A(10)=-4+(10-1)(5) | | 4(7-3a)=33 | | a(a+1)=552 | | 3m(4m+1)=12(m^2-8) | | x-2y=300 | | 27-6x=57 | | Z-2-4z=1 | | (-2x^4)(5x^3)= | | (36x+55y)+(-16x+48y)= | | -82+5-22-4+52= | | 4x^2+6x-4x^2= | | (1-x)*ln(9)=(2*x+9)*ln(3) | | -10+4x=-7 | | 3x+30+2x-10+x-6+x-4=360 | | m=-1/10,(-9,0) | | (16x+6y)+(46x+35y)= | | 5z^2-5z=0 | | 2x-3(x-4)=5(x-1)-1 |